2010
DOI: 10.1093/toxsci/kfq105
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Exposure to a Commercial PBDE Mixture, DE-71: Neurobehavioral, Hormonal, and Reproductive Effects

Abstract: Developmental effects of polybrominated diphenyl ethers (PBDEs) have been suspected due to their structural similarities to polychlorinated biphenyls (PCBs). This study evaluated neurobehavioral, hormonal, and reproductive effects in rat offspring perinatally exposed to a widely used pentabrominated commercial mixture, DE-71. Pregnant Long-Evans rats were exposed to 0, 1.7, 10.2, or 30.6 mg/kg/day DE-71 in corn oil by oral gavage from gestational day 6 to weaning. DE-71 did not alter maternal or male offspring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
128
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(146 citation statements)
references
References 75 publications
15
128
3
Order By: Relevance
“…Alterations of locomotor behavior could be due to changes to the functions of genes and proteins in the central nervous system or by direct neurotoxic effects on neuronal cells (Chen et al, 2012b). PBDEs can cause neurobehavioral alterations in rodent models (Eriksson et al, 2002;Kodavanti et al, 2010). Recently, locomotor behavior was used as an approach to study the neurobehavioral effects of PBDEs in zebrafish (Chen et al, 2012b;Chou et al, 2010;He et al, 2011;Usenko et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Alterations of locomotor behavior could be due to changes to the functions of genes and proteins in the central nervous system or by direct neurotoxic effects on neuronal cells (Chen et al, 2012b). PBDEs can cause neurobehavioral alterations in rodent models (Eriksson et al, 2002;Kodavanti et al, 2010). Recently, locomotor behavior was used as an approach to study the neurobehavioral effects of PBDEs in zebrafish (Chen et al, 2012b;Chou et al, 2010;He et al, 2011;Usenko et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have shown neurobehavioral alterations in rodent models upon exposure to PBDEs. 48,49 Recently, locomotor behavior approaches have also been performed to study the neurobehavioral effects of PBDEs in zebrafish. 29,50 Neurobehavior is an integrated response of many physiological and biochemical processes.…”
Section: Environmental Science and Technologymentioning
confidence: 99%
“…9 Exposure of the PBDE mixture DE-71 to zebrafish embryos/larvae has also been shown to result in a reduction of T4 in the larvae. 10 Like other lipophilic organic compounds, maternal transfer of several PBDEs has previously been observed in various species, such as frogs, 11 birds, 12,13 rats, 14 and humans. 15 Recently, maternal transfer of PBDEs to the offspring following parental exposure via feed was observed in zebrafish in laboratory experiments 16 and in the field.…”
Section: ' Introductionmentioning
confidence: 96%